A laboratory-based study on interspecific interactions between two stored-grain insect pests - Majumder, Rajib (Ecological Questions, 2026)
An attempt has been made to study the interspecific interaction between two stored-grain insect pests. In the laboratory, Sitophilus oryzae (Linnaeus, 1763) and Tribolium castaneum (Herbst, 1797) were allowed to rear in the same culture box containing healthy wheat grains. S. oryzae with a rostrum feeds on whole grains, whereas T. castaneum without a rostrum feeds on grain powder and often enters grooves inside the grains that S. oryzae had previously attacked. Multiple culture boxes were maintained for observation in the biological oxygen demand incubator at an optimal temperature range of 28 ± 1°C for 2 months, until the wheat grains were ground into powder. T. castaneum was predominantly detected in the grain powder, while S. oryzae was mostly found to leave the culture. Subsequently, T-tube experiments with this powder or with whole wheat grains and both insect pest species were carried out, wherein S. oryzae was observed to avoid the powder, whereas T. castaneum was attracted to it. Additionally, grain powder underwent microbiological examination using the carbol fuchsin method. This study suggests that controlling S. oryzae automatically reduces T. castaneum, a secondary pest that feeds on food damaged or broken by the former.